KONDISI PADANG LAMUN DI SEKITAR PERAIRAN MOKUPA KECAMATAN TOMBARIRI KABUPATEN MINAHASA - Meilin Yulita Walo; Calvyn F. A. Sondak; Darus Sa’adah Johanis Paransa; Janny D. Kusen; Joshian N. W. Schaduw; Billy T. Wagey; Jetty Rangan (Sam Ratulangi University, 2022)
Seagrass is the only flowering marine plant that lives permanently in shallow coastal waters and plays a key ecological role. This study aims to determine the types of seagrasses, community structure and current condition of seagrass beds nearby Mokupa waters. The method that used in this studywas the line transect method. This study found 5 types of seagrass and identified as : Enhalus acoroides, Halophila ovalis, Thalassia hemprichii, Cymodocea rotundata, and Syringodium isoetifolium. The average species density value was 25 ind/m², frequency was 1.26, species cover is 25.5. The highest important value index (INP) belongs to Cymodocea rotundata (101.5%). The diversity index (H’) was moderate with an average value of 1.17 and the dominance index is low with an average C value of 0.32. Based on the seagrass cover category, the seagrass beds in the study area were categorized as